The impact of female overlapping audit committee member on earnings management in Nigeria - Musa Nura, Dakata; Kamardin, Hasnah; Abdul Malak, Siti Seri Delima (2016)
Managers have been managing earnings especially through accruals for their personal benefits.This led to collapse of companies and loss of investments around the world.Audit committee is identified as an internal corporate governance mechanism that can monitor the managers and mitigate earnings management though with mixed result.The focus of this study is to examine whether female audit committee member who is also members of other board committee have a role in curbing opportunistic earnings management.However, some argue that gender has no additional value and overlapping overburden the audit committee members, which affect their monitoring performance and ability to mitigate earning management.This study uses modified Jones model as a proxy for earning management and document how inclusion of female overlapping director in an audit committee mitigates opportunistic earning management.